The Implementation of Kahoot! Application as a Hots-Based Evaluation Media for Elementary School Students (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The Program for International Student Assessment (PISA) states that students in Indonesia have low-level thinking skills in the international education arena. Certainly, this poses a significant challenge for the government and educators to improve the quality of education. One of the programs undertaken by the Ministry of Education and Culture is the Higher Order Thinking Skill (HOTS) based learning program. Alongside the development of technology and information, this also impacts the education sector, which must adapt to technological advancements. Continuous innovations in teaching and learning, including innovations in assessment methods, are emerging. One way of evaluating learning that teachers can use is the Kahoot application. This research aims to demonstrate how the utilization of the Kahoot application serves as a learning evaluation tool in elementary schools. The research method used is qualitative description with data collection through interviews and questionnaires. The subjects of this research are sixth-grade teachers and students in Public Elementary Schools in East OKU District. The results of the research indicate that the utilization of the Kahoot application represents a new innovation in the field of education. The Kahoot application makes it easier for teachers to assess students' problem-solving performance and creates an enjoyable learning process that encourages students to think critically.